POTENTIAL EUTROPHICATION ASSOCIATED WITH PHOSPHORUS INPUTS FROM SHRIMP EFFLUENTS IN A TROPICAL ESTUARY - Aquino, Rafael Fernando Oliveira; Rodrigues, Suzan Waleska Pequeno; Souza-Filho, Pedro Walfir Martins; Kawakami, Silvia Keiko (Geochimica Brasiliensis, 2021)
Shrimp farming has been associated with eutrophication due to the generation of effluents enriched with organic matter and nutrients. Phosphorus (P) distribution was investigated in the Coreaú River Estuary (NE Brazil) using surface sediments and sediment cores. In surface sediments, total P concentrations ranged from 349.2 to 633.5 μg g-1 (mean = 465.2) and were about three times lower than those of other Brazilian estuaries impacted by larger shrimp cultures. The predominance of P forms in surface sediments followed the sequence: iron-bound P (Fe-P, 30%) > organic-P (Org-P, 23%) > exchangeable-P (Exch-P, 20%) > authigenic apatite (Ca-P, 15%) > detrital apatite (De-P, 12%). No significant correlation was observed between Exch-P and Fe-P (r = 0.389; p < 0.05). Highest Exch-P and Org-P concentrations and a strong correlation between these forms were found (r = 0.706, p < 0.05), suggesting the same sources of P and organic matter. Total P accumulation along the cores was 10,211 and 15,632 μg g-1 at the estuary mouth (T1) and the upper estuary (T2), respectively. T1 exhibited the predominant sequence: De-P (36%) > Ca-P (25%) > Fe-P (22%) > Exch-P (9%) > Org-P (7%); whereas T2 showed: Fe-P (31%) > De-P (23%) > Org-P (21%) > Ca-P (17%) > Exch-P (9%). Phosphorus depositional history points to P accumulation episodes at the end of the 1980 and mid-1990, coinciding with increasing urbanization and the beginning or maximum activity of the shrimp farms. Despite the low total P concentrations, the proportions of the labile forms Exch-P, Fe-P and Org-P in surface sediments indicated a trend to a high potential for eutrophication.